PERAN OMBUDSMAN TERHADAP PERLINDUNGAN KONSUMEN TERKAIT LONJAKAN TAGIHAN AIR PT. PDAM KOTA MEDAN - Elvira Fitriyani Pakpahan; Henny Yulieta Sinurat; Nurhasanah Fauziah Tanjung (Legal Standing : Jurnal Ilmu Hukum, 2022)
The number of cases of law violations committed by producers who ignore the rights of consumers for their own benefit, Consumer Protection is one of the legal developments in Indonesia. However, because customers have limited legal knowledge, business actors always make customers prey. Especially in the event of a surge in clean water bills carried out by the clean water supply agency PT. PDAM in Medan City which just happened in 2021. The surge in water bills was due to a system shift that occurred because PDAM officers did not record meter readings correctly. The purpose of this study is to identify and understand consumer protection in this event and the role of the Ombudsman as a public service institution in Indonesia. The method used is an empirical juridical approach, namely conducting interviews and distributing google form questionnaires. The Consumer Protection Act does not regulate water payment provisions but has guaranteed the position of power and obligation between the two parties. The community as consumers/customers of PDAM is a party that can be protected by the Ombudsman in terms of the treatment of the public administration unit, namely PDAM, for services that are detrimental to the customer community. The role of the Ombudsman is that the implementation of public services fulfills its obligations so that consumer rights are fulfilled.